PENGARUH LINGKUNGAN KERJA, KEPUASAN DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN DINAS PERDAGANGAN KABUPATEN KEDIRI - Ayodya, Frisma Ayu; Kurniawan, Rony; Sugiono, Sugiono (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The research objective is to identify the factors influencing employee performance. In this study the independent variable is employee performance, while the independent work environment, and workload at the Department of Trade Kediri Regency. The population used is all employees and the sample in this study is 60 employees. The method used is the 5% multiple linear regression analysis technique as the overall level of confidence regarding the relationship between one variable and another. The results of the partial test prove that the variance of the work environment and workload significantly affects employee performance. Meanwhile, it has a simultaneous effect on employee performance at the Kediri Regency Trade Office